2015
DOI: 10.1107/s1600577515016938
|View full text |Cite
|
Sign up to set email alerts
|

A modular and compact portable mini-endstation for high-precision, high-speed fixed target serial crystallography at FEL and synchrotron sources

Abstract: A portable sample viewing and alignment system is described which provides fast and reliable motion positioning for fixed target arrays at synchrotrons and free-electron laser sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 22 publications
0
66
0
Order By: Relevance
“…So far, such experiments have been performed in step-scanning mode, rendering them less efficient than other sample delivery methods due to the relatively long data collection times 34,38 . Another obstacle for fixed-target experiments is the relatively high background scattering level, mainly caused by air scattering from the direct beam.…”
Section: Introductionmentioning
confidence: 99%
“…So far, such experiments have been performed in step-scanning mode, rendering them less efficient than other sample delivery methods due to the relatively long data collection times 34,38 . Another obstacle for fixed-target experiments is the relatively high background scattering level, mainly caused by air scattering from the direct beam.…”
Section: Introductionmentioning
confidence: 99%
“…A fixed target method is now capable of delivering crystals at the repetition rates of the existing XFEL sources [50] . Microfluidic flow cells would be useful for precious protein samples [51,52] .…”
Section: Discussionmentioning
confidence: 99%
“…All of the above data were recorded using the CSPAD detector. Diffraction patterns from myoglobin crystals crystallized in space group P2 1 2 1 2 1 provided an example of an orthorhombic space group and were recorded using a Rayonix MX170-HS detector at the XPP endstation using an alternative siliconchip delivery system (Sherrell et al, 2015;Zarrine-Afsar et al, 2012;Mueller et al, 2015), which has been shown to support structure solution (Oghbaey et al, 2016).…”
Section: Data Acquisition For Various Protein Crystalsmentioning
confidence: 99%